HUBUNGAN STRATEGI BISNIS FASTFOOD MELALUI DIRECT MARKETING STUDI KASUS CALIFORNIA FRIED CHICKEN SUZUYA MALL RANTAUPRAPAT - Dalimunthe, Ummi Nurzannah; Nasution, Ade Parlaungan; Lubis, Junita (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
The application of direct marketing can generally increase sales of products and services to consumers because these activities will directly obtain a response or feedback from consumers. The purpose of this study is partially independent variables Product Quality (X1), Product Attributes (X2), Service (X3) and Differentiation (X4) affect the dependent variable Direct Marketing (Y). The research design relevant to this research emphasizes descriptive research collaboration with a quantitative approach. The population and sample are customers who visit California Fried Chicken (CFC) Suzuya Mall Rantauprapat in the January-February 2023 period. The method of determining the population and sample generally uses Maximum Likehood Estimation (MLE), the number of samples in the survey ranges from 100-200 samples estimated based on the number of variable indicators as a whole 5 x 20 (indicators), so the sample set is 250 samples. The sampling technique uses purposive sampling (ie whoever the respondent is who kebutulan meets with the researcher at the California Fried Chicken (CFC) Suzuya Mall Rantauprapat). The scale technique used by the author chooses a Likert scale. As for data analysis techniques in solving problems with the Smart PLS v.4.0 application to predict the model tested in the study. From the results of the study it can be concluded that the variables of product quality (X1) and service (X3) have no significant effect on direct marketing and product attributes (X2) and differentiation (X4) have a significant effect on direct marketing. In addition, the findings of the research direct marketing variable has a good role as the dependent variable